Faktor-Faktor yang Mempengaruhi Kejadian Pneumonia pada Balita di Wilayah Kerja Puskesmas Guntung Payung Tahun 2013 - M. Noor; Sugeng Riyanto; Mutiara Kusuma Wardani; STIKES Husada Borneo; Alumni STIKES Husada Borneo (HB PRESS, 2014)
Pneunomia is infection in lower respiratory tract and it is a health problem in the world because of its high number of death, predicted more than 2 million of children under five years death because of pneumonia compared to other diseases. Pneumonia on baby and children under five years caused by bacteria and virus andinfluenced by some factors, such as environmental factor,child individual factor and behavioral factor. Environmental factors consist of house condition covers density of the house, ventilation, humidity, lighting, and air pollution in the house. For child individual factors cover child age, birth weight, nutritional status, immunization status, and giving vitamin A. Behavioral factors cover parents’ knowledge, immediate action to disease and coverage of health services. This study aimed to know the factors which influenced pneumonia occurrence on children under five at working area of Guntung Payung Health Center of Banjarbaru in 2013. This study used analytic survey method with cross-sectional approach. Population in this study was all children under five in working area of Guntung Payung Health Center of Banjarbaru in 2013 with 92 respondents. Based on the result of chi-square test showed there was no correlation among, age, birth weight and giving vitamin A with pneumonia occurrence on children under five age. Whereas, there was correlation between immunization status of children under five and pneumonia occurrence at Guntung Payung Health Center of Banjarbaru in 2013.